Pemanfaatan Chat GPT, Canva, dan Media Pembelajaran Interaktif untuk Peningkatan Kompetensi Pendidik - Dwiyono, Yudo; Wahyudi, Nova; Tannarong, Yudhy (Communio: Jurnal Pengabdian Kepada Masyarakat, 2024)
There are many challenges faced by elementary school educators/teachers in the era of the industrial revolution 4.0, especially in Samarinda. One of them is the challenge in updating learning methods in accordance with technological developments, namely the use of information and communication technology (ICT) in learning. The aim of this PKM is to increase the knowledge, understanding and skills of educators in using Chat GPT, Canva and Interactive Media to increase competence. The method used is a seminar/workshop which includes: lecture, question and answer, discussion, assignment, guided practice/exercise or mentoring. The PKM results show that this training can improve teacher competence, namely in the use of Chat GPT, Canva and learning media. Educators can create more interesting learning scenarios, can design more informative visual teaching materials; create interactive learning media. By utilizing this innovative technology, it is hoped that it can improve the quality of learning at the primary and secondary school levels and make a positive contribution to improving the quality of education in the future.